Bioquality hotspots in the tropical African flora - Marshall, C; Wieringa, J; Hawthorne, W (Cell Press, 2016)
Identifying areas of high biodiversity is an established way to prioritize areas for conservation [1–3], but global approaches have been criticized for failing to render global biodiversity value at a suitable scale for local management [4–6]. We assembled 3.1 million species distribution records for 40,583 vascular plant species of tropical Africa from sources including plot data, herbarium databases, checklists, and GBIF, and cleaned the records for geographic accuracy and taxonomic consistency. We summarised the global ranges of tropical African plant species into four, weighted, categories of global rarity called Stars. We applied the Star weights to summaries of species distribution data at fine resolutions to map the bioquality (range restricted global endemism) of areas [7]. We generated confidence intervals around bioquality scores to account for the remaining uncertainty in the species inventory. We confirm the broad significance of the Horn of Africa, Guinean forests, coastal forests of east Africa, and Afromontane regions for plant biodiversity, but reveal also the variation in bioquality within these broad regions and others, particularly at local scales. Our framework offers practitioners a quantitative, scalable and replicable approach for measuring the irreplaceability of particular local areas for global biodiversity conservation, and comparing those areas within their global and regional context.